STANDAR MUTU PENDIDIKAN ISLAM DALAM PERSPEKTIF AKREDITASI DAN TATA KELOLA KELEMBAGAAN - M. Agung Rif’at Syauqi; David Fernanda (Universitas Islam Bunga Bangsa Cirebon, 2024)
Interpersonal conflict within Islamic educational institutions constitutes a persistent yet underexamined Quality standards in Islamic education represent a critical and contested domain wherein national accreditation requirements, Islamic educational philosophy, and institutional governance practices converge with considerable complexity. Despite the Indonesian government's substantial investment in developing accreditation instruments for madrasah and Islamic educational institutions through the National Accreditation Board, persistent evidence indicates that accreditation processes frequently fail to capture the distinctive qualitative dimensions of Islamic educational excellence. This study investigates Islamic educational quality standards through the dual lens of accreditation and institutional governance, pursuing three objectives: (1) to critically analyze the conceptual architecture of Islamic educational quality standards and their relationship with accreditation frameworks, (2) to examine the gaps between accreditation-based quality measurement and authentic Islamic educational quality, and (3) to formulate an integrated quality governance model that reconciles accreditation requirements with holistic Islamic educational excellence. Employing a systematic library research methodology drawing on thirty-four peer-reviewed sources published between 2020 and 2025, the study proposes the Islamic Holistic Quality Governance Framework (IHQGF), a five-dimensional model integrating substantive Islamic educational quality with rigorous governance accountability mechanisms.